Community engagement journey at Kampung Sungai Pusu, Gombak - Mhd. Sarif, Suhaimi (Sejahtera Centre for Sustainability and Humanity IIUM, 2023)
The narrative presented in this chapter is structured around two unique modules referred to as "Usrah in Action 1" and "Usrah in Action 2." During the intial stage at Usrah in Action 1, students commenced an exploration aimed at comprehending the intricacies of a particular community through the process of completing thorough community profiling. The "Usrah in Action 2" used the community profiling findings to organize community engagement programs.